PENERAPAN KEBIASAAN BARU TERKAIT COVID-19 PADA MASYARAKAT ADAT DI KELURAHAN DUFA-DUFA KECAMATAN TERNATE UTARA - Masni A. Kadir; Ramli * (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2020)
The adaptation of new normal is actually an effort to maintain good habits that guide the Covid-19 protocol. The habit of wearing masks, avoiding crowds, keeping your distance, and frequently washing your hands with soap have become new habits in community life. The main objective of this research is the application of adaptation to new normal related to covid-19 traditional communities in the Dufa-Dufa village. The method used in this research is qualitative. How to get data using interviews, documents, and observations. Further analysis is carried out, then the data is interpreted and presented in a narrative form. The results showed that in general the traditional communities of Dufa-Dufa village had known about the adaptation of new habits but had not followed it in depth. The community has not been effective and maximally implemented the Covid-19 health protocol in the form of the habit of wearing masks, avoiding crowds, maintaining distance, and frequently washing hands with soap.